Effect of two 12-minute culturally targeted films on intent to call 911 for stroke. (24th May 2016) - Williams, Olajide; Leighton-Herrmann, Ellyn; DeSorbo, Alexandra; Eimicke, Joseph; Abel-Bey, Amparo; Valdez, Lenfis; Noble, James; Gordillo, Madeleine; Ravenell, Joseph; Ramirez, Mildred; Teresi, Jeanne A.; Jean-Louis, Girardin; et al.
Abstract : Objective: We assessed the behavioral effect of two 12-minute culturally targeted stroke films on immediately calling 911 for suspected stroke among black and Hispanic participants using a quasi-experimental pretest-posttest design. Methods: We enrolled 102 adult churchgoers (60 black and 42 Hispanic) into a single viewing of one of the 2 stroke films—a Gospel musical (English) or Telenovela (Spanish). We measured intent to immediately call 911 using the validated 28-item Stroke Action Test in English and Spanish, along with related variables, before and immediately after the intervention. Data were analyzed using repeated-measures analysis of variance. Results: An increase in intent to call 911 was seen immediately following the single viewing. Higher self-efficacy for calling 911 was associated with intent to call 911 among Hispanic but not black participants. A composite measure of barriers to calling 911 was not associated with intent to call 911 in either group. A significant association was found between higher stroke symptom knowledge and intent to call 911 at baseline, but not immediately following the intervention. No sex associations were found; however, being older was associated with greater intent to call 911. The majority of participants would strongly recommend the films to others. One participant appropriately called 911 for a real-life stroke event. Conclusions: Narrative communication in the form of tailored short films may improve intent to call 911 for stroke among the black and Hispanic population.